Investigation of the jumper parameters action on microstrip Langue coupler characteristics - Фарафанов, А.Ю.; Фурманова, Н.И. (Radiotekhnika, 2012)
Directional Langue couplers are widely used in electronic equipment. A feature of these microstrip couplers is the existence of wire jumpers. Investigation of the action of the microstrip directional Langue couplers jumpers’ parameters on the frequency response is carried out. Recommendations for the modeling of such structures in the HFSS are given. The dependence of Langue coupler frequency response on the diameter, material, and the number of jumpers is analyzed. Practical advice on jumper parameters when designing, simulation and manufacturing of the microstrip directional Langue couplers is presented.